QARAQALPAQ XALÍQ QOSÍQLARÍNDA «BAWÍR» KONCEPTINIŃ LINGVOMÁDENIY ANALIZI - Qayıpnazarova, U. (SCIENCE and SOCIETY, 2025)
The article examines the concepts of "liver" in the spoons of the Karakalpak people, reveals somatic phraseology and somatisms in the customs of the Karakalpak people.